Нітроксидергічний дисбаланс та вільнорадикальна модифікація білків у структурах проміжного мозку щурів з експериментальним цукровим діабетом за умов гострого порушення кровообігу в басейні сонних артерій - Бойчук, Т.М.; Савчук, Т.П. (Таврический медико-биологический вестник, 2012)
Сахарный диабет снижает содержание метаболитов оксида азота и продуктов окислительной модификации белков во всех исследованных структурах промежуточного мозга. Каротидная ишемияреперфузия увеличивает содержание метаболитов оксида азота, более существенно – у животных с диабетом, а также содержание продуктов окислительной модификации белков в перегородке мозга крыс с диабетом. Diabetes mellitus reduces the content of nitric oxide metabolites and products of oxidative modification of proteins in all the investigated structures of the diencephalon. Carotid ischemia-reperfusion in all brain regions increases levels of nitric oxide metabolites, more significantly - in animals with diabetes mellitus, as well as the content of products of oxidative modification of proteins in brain septum in rats with diabetes.